Efektivitas preceptorship terhadap kinerja klinik mahasiswa: Literature review - Anitha Bunga Manginte; Rini Rachmawaty; Ariyanti Saleh (Jurnal Keperawatan Muhammadiyah, 2019)
Nowadays, the demands for health services are increasing, health problems are increasingly complex, the development of science and nursing technology is increasingly sophisticated, and the requirements of the workforce are increasingly demanding nursing staff to be competent. Therefore, nursing education institutions are required to be able to prepare graduates who are competent and able to compete both nationally and internationally. In education field, one of efforts of the Association of Indonesian Nurse Education Center (AINEC) to developing competent Ners graduates is by applying a preceptorship guidance model. But there are still a few articles that discuss the method of guidance in the preceptorship that can be used by preceptors to improve the  clinical performance of student. The aim of this literature review is to identify the method of guidance in the preceptorship that can be used by preseptors to improve the clinical performance of student. This literature review examines the methods in the preceptorship that are used to improve student clinical competencies (decision-making abilities, communication skills, practical skills, and social skills). The article search was carried out on databases Pubmed and Google Scholar, using  keywords preceptorship, nursing students, clinical learning, clinical performance, decision making abilities, communication skills, practice skills. The number of articles reviewed was 15 articles. In preceptorship, to improved the student ability of decisions making can by using case discussion methods, bed side teaching, nursing rounds, and pre and post conference. Communication skills can be improved by case discussions, rounds, bed side teaching, role modeling, and pre and post conferences. Student practice skills can be improved by the method of bedside teaching and demonstration. And social skills can be improved by role modeling. Based on this literature review, it can be concluded that the guidance methods used in the preceptroship are useful for improving the competency of student clinics. Therefore, it is important for the preseptor to know what methods can be used in guiding according to the competencies that are to be improved on students.